The strategies implemented by OSK company and its effect on investment during the bear market / Alisa Alice Fredly - Fredly, Alisa Alice (Faculty of Business and Management, 2010)
This case studies on company performance during economic crisis on OSK investment Bank. The scope only focuses on the strategies implemented and its effect on investment during recession. The objective of the study is to identify the result and the effects of investing in market down since bear market is a part of the market cycle. Financial ratio analysis and graph can be used as the indicator to measure the financial performance in term of profitability, debt and stock market ratios performances by understanding the relationship between economic conditions with financial performance. The data period take by the time of recession and end of economic crisis, from 2008 to 2009 (one year). The results from financial ratios analysis shows a positive growth shown on their operating revenue that indicated their core businesses were not affected amid economic downturn. This is because investment becomes most activities business for Malaysian now days.